(untitled) (Research, Society and Development, 2021)
This study aims to describe the epidemiological profile of patients co-infected with HTLV-1 and Strongyloides stercoralis, from the Center for Tropical Medicine (NTM) located at the Federal University of Pará (UFPA). A quantitative, retrospective and cross-sectional analysis was performed, using information from patients with HTLV-positive serology, confirmed by the Polymerase Chain Reaction (PCR) for HTLV-1 or HTLV-2, in addition to parasitological tests confirmed by the Hoffman method. Of the 4.679 patients examined, 538 positive samples were detected, 432 for HTLV-1 (80%) and 106 (20%) for HTLV-2. In the parasitological examination, 14 samples positive for S. stercoralis and 81 negative were obtained from a total of 95 patients who took their material for analysis, were it was possible to determine a 14,7% of coinfection prevalence’s between the two infectious agents. There was a predominance of HTLV-1 positive female patients over male patients. This can occur due to the ease of transmission through sexual intercourse and also to the hormonal effects of women, making them more susceptible to infection. From that, it was found that many patients with HTLV-1/2 may also have co-infection with S. Stercoralis, especially in the state of Pará.